2015
DOI: 10.1016/j.canep.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

European Code against Cancer 4th Edition: 12 ways to reduce your cancer risk

Abstract: This overview describes the principles of the 4th edition of the European Code against Cancer and provides an introduction to the 12 recommendations to reduce cancer risk. Among the 504.6 million inhabitants of the member states of the European Union (EU28), there are annually 2.64 million new cancer cases and 1.28 million deaths from cancer. It is estimated that this cancer burden could be reduced by up to one half if scientific knowledge on causes of cancer could be translated into successful prevention. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
140
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 200 publications
(166 citation statements)
references
References 27 publications
(21 reference statements)
0
140
0
16
Order By: Relevance
“…2,3 The EU Council in a series of recommendations published in 2003, urged the Member States to introduce or scale up breast, cervical and colorectal cancer screening through systematic population-based approach with quality assurance at all levels. 4 The first report on the implementation of the Council recommendations prepared by the International Agency for Research on Cancer (IARC) concluded that the number of individuals having access to population-based screening in the year 2007 was much lower than the desired level and substantial opportunistic screening was ongoing in the Member States, targeting nearly 100 million men and women.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 The EU Council in a series of recommendations published in 2003, urged the Member States to introduce or scale up breast, cervical and colorectal cancer screening through systematic population-based approach with quality assurance at all levels. 4 The first report on the implementation of the Council recommendations prepared by the International Agency for Research on Cancer (IARC) concluded that the number of individuals having access to population-based screening in the year 2007 was much lower than the desired level and substantial opportunistic screening was ongoing in the Member States, targeting nearly 100 million men and women.…”
mentioning
confidence: 99%
“…2 In Austria a population based screening programme is implemented only in the state of Burgenland, since 2003. In the rest of the country screening is opportunistic.…”
mentioning
confidence: 99%
“…The risk of cancer increases depending on alcohol dose in combination with biological mechanisms, where ethanol and its genotoxide metabolism and acetaldehyde play an important role [30]. When consuming 10g of ethanol daily the risk of breast cancer increases by 8% in the postmenopausal period, by 9% before menopause and by 10% in general [31].…”
Section: Diet In 2007 World Cancer Research Fund / Americanmentioning
confidence: 99%
“…A kódex harmadik, majd negyedik revíziója [10,11] tekintetbe veszi a tudományos kutatások újabb eredményeit (például HPV elleni oltás), és a korábbi "Tízpa-rancsolatot" 12 ajánlássá bővítve adja közre (1. táblázat).…”
Section: Az Európai Rákellenes Kódexunclassified